2012
DOI: 10.3109/13561820.2011.628425
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an interprofessional standardized patient exercise on attitudes toward working in interprofessional teams

Abstract: Effective interprofessional education engages participants in authentic tasks, settings and roles. Using these guiding principles, an interprofessional standardized patient exercise (ISPE) was developed and implemented for 101 dental, medical, nurse practitioner, pharmacy and physical therapy students. This study describes the ISPE and evaluates its impact on students' attitudes toward working in interprofessional teams. The attitudes toward health care teams (ATHCT) survey was administered pre- and post-ISPE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 19 publications
3
57
1
Order By: Relevance
“…The Attitudes Toward Health Care Teams Scale (ATHCTS) has been used in ten studies measuring attitudes towards interprofessional collaboration in a variety of settings, most commonly interprofessional education. [58][59][60][61][62][63][64][65][66][67] It consists of three subscales assessing attitudes about team value, team efficiency and the physician's shared role on the team. ATHCTS 65 The Ottawa Global Rating Scale has been used in multi-specialty education as an objective measurement of an individual's crisis resource management skills in simulated scenarios.…”
Section: Description and Validity Evidence For Teamwork Assessment Toolsmentioning
confidence: 99%
“…The Attitudes Toward Health Care Teams Scale (ATHCTS) has been used in ten studies measuring attitudes towards interprofessional collaboration in a variety of settings, most commonly interprofessional education. [58][59][60][61][62][63][64][65][66][67] It consists of three subscales assessing attitudes about team value, team efficiency and the physician's shared role on the team. ATHCTS 65 The Ottawa Global Rating Scale has been used in multi-specialty education as an objective measurement of an individual's crisis resource management skills in simulated scenarios.…”
Section: Description and Validity Evidence For Teamwork Assessment Toolsmentioning
confidence: 99%
“…Our study design addressed the need outlined in the Garling Report (Garling 2008) to provide these clients with effective holistic client centred care by deliberately developing eight simulation scenarios selected from actual cases of social care clients with complex chronic conditions. More specifically, our project combined IPE with scenario-based education (SBE) and as such our results might be more closely compared with more recent studies of IPE programs developed by HEPS which have similarly utilised SBE to deliver IPE programs for undergraduates (Shrader et al 2013, Kyrkjebo et al 2006, Vyas et al 2012, Wamsley et al 2012, and Kilminster et al 2004. Our study was different in respect of the use of volunteer SCs, the rural setting in community health, and the pairing of different disciplines to collaborate in a simulated intake interview.…”
Section: Discussionmentioning
confidence: 74%
“…Recent reports of combined IPE/simulation team training using high fidelity mannequins (Shrader et al 2013), standardised patients (Wamsley et al 2012), or hybrid simulations (Shrader et al 2013, Kilminster et al 2004, and Vyas et al 2012 suggest outcomes include improved understanding of roles of other professionals and increased awareness of the importance of interprofessional communication for patient safety. Further, Shrader et al (2013) found that effective interprofessional teamwork is associated with positive clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Small group interaction, discussion, and collaborative learning have been favored as part of the IPE model to enhance student satisfaction with their learning experience. [13,[16][17][18] Previous studies reported that IPE initiative commonly includes group sizes of between 5 to 10 students to facilitated quality interactions. [19] Group balance and stability, such as an equal mix of professionals and little "turnover" of group members (in terms of established members leaving and new ones joining), are also important for student interaction and learning process.…”
Section: Discussionmentioning
confidence: 99%